Effects on bread and oil quality after functionalization with microencapsulated chia oil - González, Agustín (2018)
BACKGROUND: Omega-3 and omega-6 fatty acids-rich oils suffer oxidation reactions that alter their chemical and organoleptic quality. Microencapsulation can be a powerful tool for protection against ambient conditions. In the present study, the addition of microencapsulated chia oil as an ingredient in bread preparations and its effect on the technological and chemical quality of breads was investigated. RESULTS: Microencapsulation of chia oil was carried out by freeze-drying with soy proteins as wall material and oil release was determined under in vitro gastric and intestinal conditions. Encapsulated oil-containing bread showed no differences in specific volume, average cell area, firmness and chewiness with respect to control bread. Unencapsulated oil-containing bread showed a marked increase in hydroperoxide values respect to control, whereas encapsulated oil-containing bread values were not affected by baking and bread storage. The fatty acid profiles showed a decrease of 13% and 16%, respectively, in α-linolenic acid in the encapsulated and unencapsulated oils with respect to bulk chia oil. Sensory analysis showed no significant differences between bread samples. CONCLUSION: The addition of encapsulated chia oil did not alter the technological quality of breads and prevented the formation of hydroperoxide radicals. A ration of encapsulated oil-containing bread contributes 60% of the recommended dietary intake of omega-3 fatty acids.